Synthetic analogues of Fe(ii)–Fe(iii) minerals containing a pentagonal 'Cairo' magnetic lattice. Issue 29 (30th June 2016) - Cumby, J.; Bayliss, R. D.; Berry, F. J.; Greaves, C.
Abstract : Synthesis, properties and chemical modification of low-dimensional minerals. Abstract : Versiliaite and apuanite are two minerals containing Fe 2+ and Fe 3+ in a low-dimensional structure exhibiting chains of edge-linked FeO6 octahedra. The chemistry of these minerals has not been fully examined because of their rarity. We demonstrate that chemical synthesis of these minerals is possible to allow measurement of their magnetic properties and a more complete description of their structural features using neutron powder diffraction. We also show that chemical manipulation is possible to provide isostructural phases with different chemical compositions.